Pakistan: One Year Growth Strategy (The Pakistan Development Review, 2025)
• Focus on Investment, productivity, and exports.• Remove bottlenecks linked to terrifs, sludge: cost of regulation, financial &energy constraints.• Initiate “Regulatory Audit”.• Reduce bank’s holding of the government securities.• Create a National Debt Management Office.• Revisit DISCO’s management.• Introduce pre-paid metering.• Do away from uniform energy tariffs.• Introduce wheeling and bilateral agreements.• Tax Simplification• Implement Point of Sale (POS)• Deregulate the real estate market by eliminating NOCs and FBR/DC rates.• Tie Real estate & city development.• Unlock dead capital.• Internet for all.• Youth Involvement—promote sports, culture & clubs• Promote street vending—huge employment generation.